Means for Optimizing Skills’ Formation Process In Order To Make Arithmetic Calculations, Equations and Graphs in English by Students of Economic Specialties - Касьянова, Вікторія Геннадіївна; Медвідь, Марина Миколаївна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2018)
In the article it is proposed a teaching scheme which optimizes the formation of English language skills of making mathematical calculations. The scheme is based on the peculiarities of financial and accounting reports viewed from the professional English language terms, the way of presenting them, specific verbalization of common signs from other scientific fields (algebra, geometry, etc.) and considers the lack of academic hours. The scheme involves 5 stages: arithmetic operations, calculations with the help of equations, graphs, balance sheet assets and liabilities, presentations with graphs and calculations. The subject of the research is the means for optimizing skills’ formation process in English in financial and accounting fields of knowledge for the students of economics. The material of the research are those chapters of income tax returns, balance sheets, etc., in Ukrainian and English, which have calculations in equations and graphs.